A comparison of optimized deliveries by drone and truck. Issue 3 (3rd April 2021) - Choi, Youngmin; Schonfeld, Paul M.
ABSTRACT: This paper formulates and compares four alternatives of package delivery service with and without the aid of drones: (i) conventional truck, (ii) drone supported by truck, (iii) one-to-one delivery by drone, and (iv) one-to-many delivery by drone. Each delivery alternative is optimized numerically with an objective of total cost minimization (i.e. the sum of user's and operator's costs). For analyzing the delivery systems, the authors employ their recently developed distance approximation methods that estimate average tour lengths when only a few points are visited points, due to limited drone loading capacity. Analyses are conducted with respect to sensitivity to driver pay rate, demand density, user value of waiting time for delivery, drone operating speed, service area size, drone size, and distribution hub location. For reasonable baseline inputs, results indicate that using drones for package deliveries may be cost-effective compared to using conventional trucks.